Examining support of South African Defence Force conscription by the mainstream Afrikaans sister churches (1968–1991) - Gordon, Will (Scientia Militaria - South African Journal of Military Studies, 2022)
From the 1950s to the 1990s, white men were conscripted to serve in the South African Defence Force (SADF). Although it varied in its application and duration, conscription was an undeniable, and often unavoidable, part of life for white South Africa. While it was not universally accepted, and certainly not universally popular, resistance was largely confined to English-speaking citizens. Objection was often seen as cowardly or treacherous. Conscription had an influence on the psyche of white South Africa and was viewed in a serious light by various religious denominations. Ecclesiastical positions varied and often changed over the course of time. In the main, Afrikaans churches were sympathetic towards conscription, while English churches were likely to oppose it. The latter position has been extensively documented, but the former remains neglected. This article analyses the role that mainstream Afrikaans sister churches played in supporting the National Party policies of conscription and ensuring their congregants’ compliance. It also presents a discussion on the relationship between those churches and the SADF, inter alia by referring to changes in conscription legislation and the reaction of the churches to those changes.